2022
DOI: 10.3389/fcvm.2022.935524
|View full text |Cite
|
Sign up to set email alerts
|

Paroxysmal Atrial Fibrillation Originating From the Inferior Vena Cava: A Case Report and Literature Review

Abstract: Atrial fibrillation is a common arrhythmia, but atrial fibrillation originating in the inferior vena cava is extremely rare. Here, we present a case of a 51-year-old woman with symptomatic paroxysmal atrial fibrillation, who was admitted to the Second Affiliated Hospital of Dalian Medical University and underwent radiofrequency ablation. The atrial fibrillation persisted despite pulmonary vein isolation. The inferior vena cava was then identified not only as a trigger but also as the driver to maintain atrial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 14 publications
4
0
0
Order By: Relevance
“…However, a total of only 7 isolated reports (8 cases) had been reported as of July 2022. 2 , 3 , 4 , 5 , 6 , 7 , 8 In line with the rarity of previously published cases, there were only 2 cases (0.04%) among 4500 AF ablation procedures in our hospital. 4 Thus, the prevalence of AF triggers in the IVC is considered to be much lower in the real world than the recent report.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…However, a total of only 7 isolated reports (8 cases) had been reported as of July 2022. 2 , 3 , 4 , 5 , 6 , 7 , 8 In line with the rarity of previously published cases, there were only 2 cases (0.04%) among 4500 AF ablation procedures in our hospital. 4 Thus, the prevalence of AF triggers in the IVC is considered to be much lower in the real world than the recent report.…”
Section: Discussionsupporting
confidence: 81%
“…In previous reports, although 9 cases anatomically demonstrated the origin of the trigger from the IVC using a contact 3D-EAM system, the definition of the border between the IVC and RA was unclear. 1 , 6 , 7 , 8 In the present case, the concealed IVC firings (bigeminy) observed in the IVC strongly suggested an origin inside the IVC rather than at the RA-IVC junction; in addition, the reconstructed computed tomography scan also suggested that the origin was located below the Eustachian ridge ( Figure 3C ). This is the first report to reveal continuous ectopic bigeminy definitely originating from the tiny area within the IVC by mapping ectopic beats both with and without conduction to the atrium from the IVC using a 3D-EAM system.…”
Section: Discussionsupporting
confidence: 59%
“…1 However, a total of only 7 isolated reports (8 cases) had been reported as of July 2022. [2][3][4][5][6][7][8] In line with the rarity of previously published cases, there were only 2 cases (0.04%) among 4,500 AF ablation procedures in our hospital. 4 Thus, the prevalence of AF triggers in the IVC is considered to be much lower in the real world than the recent report.…”
Section: Discussionsupporting
confidence: 79%
“…In previous reports, although nine cases anatomically demonstrated the origin of the trigger from the IVC using a contact 3D-EAM system, the definition of the border between the IVC and RA was unclear. 1,[6][7][8] In the present case, the concealed IVC firings (bigeminy) observed in the IVC strongly suggested an origin inside the IVC rather than at the RA-IVC junction. This is the first case demonstrating the limited excitation area with a low voltage in the IVC by detailed 3D-EAM.…”
Section: Discussionsupporting
confidence: 53%